Abundance and Chlorophyll-a Content of Spirulina sp in Given Different Light Intensity Media’s - Sari, Sri Nadila; Syafriadiman, Syafriadiman; Hasibuan, Saberina (Faculty of Fisheries and Marine, Universitas Riau, 2024)
Spirulina sp is one of the organisms used because it has twice the chlorophyll content of the alfalfa plant, the chlorophyll of which has previously been explored. Chlorophyll-a is a photosynthetic pigment, and light is very influential in photosynthesis in microalgae cultivation because light is a crucial part of the photosynthetic pigment as a source of energy for microalgae life. The purpose of this research is to get the best light intensity. This research started in September 2022 at the Aquaculture Environmental Quality Laboratory, Faculty of Fisheries and Marine, Universitas Riau. This study used a one-factor, Completely Randomized Design (CRD) method with five treatments and three replications. The treatment in this study was the light intensity consisting of P0: without giving light, P1: 2.974 lux, P2: 4.274 lux, P3: 5.575 lux, P4: 6.877 lux. The results of this study indicate that light intensity affects the locking of Spirulina sp. The best treatment was a light intensity of 4.274 lux with a cell density of 327.176,2 ind/mL with a chlorophyll-a content of 0.4 µg/mL with a range of water quality parameters that were optimal for the growth of Spirulina sp temperature value 28-31, pH 7-8.5, DO 5-7.5